Draft Annual Plan 1987-88 Volume : II General Areas Government of Assam - Planning Commission (Planning Commission, 1987)
Modernisation of Agriculture has been one of the main thrust of the planning strategy in the state five year plans implemented, so far,, in the annual plan, 1987-88 also the basic objective is. to increase the Agriculture Production through improved agriculture practices. Since 80 percent of the population are engaged in agriculture for their livelihood the future of the rural economy and for that matter the economy of the state as a whole depends, oh the planned development of agriculture.
Government of Assam, Planning and Development Department